2011
DOI: 10.1063/1.3633100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excess oxygen on operation characteristics of amorphous In-Ga-Zn-O thin-film transistors

Abstract: Operation characteristics of amorphous In-Ga-Zn-O (a-IGZO) thin-film transistors (TFTs) were improved to a subthreshold voltage swing (S) of 217 mV (decade)−1, a mobility of ∼11.4 cm2 (Vs)−1, and a threshold voltage (Vth) of 0.1 V by O3 annealing at a temperature as low as 150 °C. However, the O3 annealing at 300 °C caused serious deterioration and exhibited a bistable transition between a large S state and a large Vth state. This transition is attributed to incorporation of excess oxygen and associated subgap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
152
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(160 citation statements)
references
References 15 publications
7
152
1
Order By: Relevance
“…Figure 3 shows the hysteresis curves in the transfer characteristics of the a-IGZO TFTs additionally annealed in O 2 for 8 h, swept for 3 cycles of V GS between ¹20 to 20 V. These transfer curves exhibited very large hysteresis loops, indicating that the TFT characteristics were deteriorated by formation of electron traps by the additional oxygen annealing; i.e., the electrons induced by the large positive V GS are captured by traps, the charged traps are energetically relaxed to an energy deeper than the Fermi level, and the V on is increased in the backward V GS sweep measurements. A similar behavior is observed by 300°C O 3 annealing, 11) but that is different from the present case because the high-V th state was stable at least for 12 h in that case; on the other hand, the high-V on state is quickly recovered to the initial small-V on state and the same forward-sweep characteristics are observed also in the 2nd and 3rd cycle measurements. That is, the clock-wise hysteresis suggests that the a-IGZO channel layer contains electron traps with a fast recovery time.…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…Figure 3 shows the hysteresis curves in the transfer characteristics of the a-IGZO TFTs additionally annealed in O 2 for 8 h, swept for 3 cycles of V GS between ¹20 to 20 V. These transfer curves exhibited very large hysteresis loops, indicating that the TFT characteristics were deteriorated by formation of electron traps by the additional oxygen annealing; i.e., the electrons induced by the large positive V GS are captured by traps, the charged traps are energetically relaxed to an energy deeper than the Fermi level, and the V on is increased in the backward V GS sweep measurements. A similar behavior is observed by 300°C O 3 annealing, 11) but that is different from the present case because the high-V th state was stable at least for 12 h in that case; on the other hand, the high-V on state is quickly recovered to the initial small-V on state and the same forward-sweep characteristics are observed also in the 2nd and 3rd cycle measurements. That is, the clock-wise hysteresis suggests that the a-IGZO channel layer contains electron traps with a fast recovery time.…”
Section: Methodssupporting
confidence: 61%
“…300°C exhibited a significant deterioration and bistable behavior. 11) On the other hand, Hall mobilities (® Hall ) and field-effect mobilities (® FE ) of a-IGZO TFTs with the chemical composition of In:Ga:Zn³1:1:1 in atomic ratio are reported to be 1015 cm 2 /Vs, 1),12) but some reports have provided much larger mobilities. Based on the device physics, ® FE should be smaller than drift mobility (³® Hall ) because ® FE include the deterioration effects by electron traps in the band gap and carrier scattering at the channelgate insulator interface; 13) actually, we have confirmed that ® FE of our a-IGZO TFTs are close to or a little bit smaller than ® Hall .…”
Section: Introductionmentioning
confidence: 99%
“…42 The SR-driven doping effect is expressed in terms of the atomic rearrangement in the devices and the changes in the density of states in a-IGZO; these factors are shown in Figures 4c and d, respectively. The density of states in a-IGZO in the as-deposited state was obtained from Kamiya et al 3 and Ide et al 43 During annealing, SR results in the densification of the a-IGZO thin-films (Figure 1e and Supplementary Figure S1c) and a decrease in the free volume in a-IGZO in association with greater V O s in the dense network. Therefore, V O s in deep-donor or electron-trap states are transformed into shallow-donor states.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the excess O can be removed using a thermal annealing process. 36,39 Because electron trapping still occurs in the absence of excess O, there should be another cause of electron trapping.…”
Section: Introductionmentioning
confidence: 99%
“…An excess O defect model has been previously suggested to describe electron-trap centers based on ozone-treated amorphous InGaZnO 4 . 39 The excess O is characterized as a weakly binding O that results in a peak at~200°C in thermal desorption spectroscopy. Thus, the excess O can be removed using a thermal annealing process.…”
Section: Introductionmentioning
confidence: 99%